COVID-19 on the Navajo Nation: experiences of Diné families of children with asthma. (4th March 2023) - Gerald, Lynn B.; Simmons, Bryan; Lowe, Ashley A.; Liu, Andrew H.; Nez, Peter; Begay, Elvira; Bender, Bruce
Abstract: Objective: The first case of COVID-19 on the Navajo Nation (NN) was found on March 17, 2020. Even with strong public health efforts, NN saw the highest per capita infection rate in the US during May of 2020 with 2450/100, 000. To determine the impact of COVID-19 on families of children with asthma on the NN, families participating in the NHLBI funded Community Asthma Program were contacted to see if they would share their experiences. Methods: Sixty-six of 193 families (34%) were interviewed. Results: The average age of the child with asthma was 13.5 (SD = 3.9) and 33% were female. Most Diné children with asthma in our study did not contract COVID-19. However, the pandemic had a significant impact on them and their families. Many family members contracted COVID-19, some children lost family members, and half of interviewed parents reported a decline in their child's mental health. Twenty-five percent of families sought the help of a traditional healer. Many accessed medical care through telehealth and most were able to obtain asthma medications when needed. Conclusions: Despite significant challenges, our research indicated resilience among Navajo families.